The Effect of Village Community Economic Empowerment on Poverty Reduction in Rantau Bayur District of Banyuasin Regency - Salim, Agus (Nusantara Journal of Behavioral and Social Science, 2022)
Community economic empowerment is an important thing to improve the village economy and also the community so that people who are still said to be poor can be empowered. One program that is expected to be able to move the wheels of the economy, especially the rural economy, is the BUMDes which has been formed in each village, in Rantau Bayur District, Banyuasin Regency. BUMDes was created by the government in an effort to alleviate poverty and improve village economic efforts based on the needs and potentials that exist in the village. The purpose of this study was to determine how much influence the economic empowerment of rural communities has on poverty alleviation in Rantau Bayur District, Banyuasin Regency. This research is a quantitative approach, using simple random aside with the data collection methods that the authors use are questionnaires (questionnaires) and documentation. The results of instrument testing were conducted on 50 respondents with a total of 33 statement items, it was declared valid and could be used to collect data on the research sample. The population in this study was the entire community of Tebing Abang Village, Rantau Bayur District, Banyuasin Regency, while the research sample amounted to 96 respondents from the Tebing Abang Village community. While the data analysis technique used is the Pearson product-moment correlation analysis technique and the simple linear regression analysis technique using SPSS 23.0. The results of this study indicate that the correlation between community economic empowerment and poverty alleviation is 0.855. Based on the level of reliability, Cronbach alpha is in the "very reliable" category. This shows that there is a very reliable relationship between community economic empowerment and poverty alleviation. In addition, the significant difference between the variables of community economic empowerment (X) and poverty alleviation (Y) is 0.005. Based on the decision rule of the hypothesis, the probability value of 0.05 is greater than or equal to the probability value of sig, or (0.05 0.005), so H0 is rejected and Ha is accepted, meaning that there is a significant effect. The coefficient of determination of 8.2% means that the influence of community economic empowerment on poverty alleviation is very small, while 91.8% is caused by other factors outside of community economic empowerment.Abstrak:Â Pemberdayaan ekonomi masyarakat merupakan suatu hal yang penting untuk meningkatkan perekonomian desa dan juga masyarakat, agar masyarakat yang masih dikatakan miskin dapat terbedayakan. Salah satu program yang diharapkan mampu menggerakan roda perekonomian, khususnya ekonomi pedesaan ialah seperti BUMDes yang sudah terbentuk di masing-masing desa Kecamatan Rantau Bayur Kabupaten Banyuasin. BUMDes dibuat pemerintah dalam upaya mengentaskan kemiskinan, meningkatkan usaha perekonomian desa berdasarkan kebutuhan dan potensi yang ada di desa. Tujuan penelitian ini adalah untuk mengetahui berapa besar pengaruh pemberdayaan ekonomi masyarakat desa terhadap pengentasan kkemiskinan di Kecamatan Rantau Bayur Kabupaten Banyuasin. Penelitian ini adalah pendekatan kuantitatif, menggunakan simple random samping dengan metode pengumpulan data yang penulis gunakan ialah kuesioner (angket) dan dokumentasi. Dari hasil uji coba instrument yang dilakukan pada 50 responden dengan jumlah 33 item pernyataan dinyatakan valid dan dapat digunakan untuk mengumpulkan data pada sampel penelitian. Populasi dalam penelitian ini adalah seluruh masyarakat Desa Tebing Abang Kecamatan Rantau Bayur Kabupaten Banyuasin, sedangkan sampel penelitian berjumlah 96 responden masyarakat Desa Tebing Abang. Sedangkan teknik analisis data yang digunakan adalah teknis analsis korelasi pearson product moment dan teknik analisis regresi liniear sederhana menggunakan SPSS 23.0. Hasil dari penelitian ini menunjukkan bahwa korelasi antara pemberdayaan ekonomi masyarakat terhadap pengentasan kemiskinan sebesar 0,855. Berdasaran tingkat keandalan cronbach alpha masuk dalam kategori â€œsangat andalâ€. Hal tersebut menunjukkan terjadi hubungan antara pemberdayaan ekonomi masyarakat sangat andal dengan pengentasan kemiskinan. Selain itu signifikan antara variabel pemberdayaan ekonomi masyarakat (X) dan pengentasan kemiskinan (Y) adalah sebesar 0,005. Berdasarkan kaidah keputusan dari hipotesis, maka nilai probalitas 0,05 lebih besar atau sama dengan nilai probabilitas sig, atau (0,05 lebih besar dari 0,005), maka H0 ditolak dan Ha diterima, artinya terdapat pengaruh yang signifikan. Nilai koefisien determinasi sebesar 8,2% artinya pengaruh pemberdayaan ekonomi masyarakat terhadap pengentasan kemiskinan sangat kecil, sedangkan 91,8% disebabkan oleh faktor lain di luar pemberdayaan ekonomi masyarakat.